SPIRIT BEYOND SELF: AN ANALYSIS OF SELF-TRANSCENDENCE IN THE MOTIVATION OF SERVICE BY TAKMIR THE JOGOKARIYAN MOSQUE - Cici Laras Jabil; Zainal Arifin; Ika Tiara Aryani; Luluk Shomitah (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2026)
This study aims to analyze the manifestation of self-transcendence in the devotional experience of a mosque caretaker at the Jogokariyan Mosque in Yogyakarta. A qualitative approach was used through in-depth interviews, observation, and documentation, with thematic data analysis techniques and source triangulation to ensure data validity. The findings indicate that the involvement of mosque caretakers iso no longer driven by fulfilling personal needs, but has transcended self-interest to serve the community and divine values. This aligns with Abraham Maslow's theory of self-transcendence, which places transcendence as the pinnacle of human motivation, when individuals direct themselves toward goals broader than personal interests. The devotion of caretakers at the Jogokariyan Mosque demonstrates that religious activities can become a space for spiritual and social actualization that produces profound inner change. Thus, the caretaker's experience reflects an integrated process of transcendence between spirituality, social concern, and self-maturation, which simultaneously serves as the foundation for the success of the mosque movement based on congregational service, as well as strengthening the role of the mosque as a center for social transformation and the formation of leadership based on transcendental values.